2020
DOI: 10.1002/adts.202000024
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dynamics Simulations on the Adsorption Mechanism of Reducing and Oxidizing Gases on the CH3NH3PbI3 Surface

Abstract: Existing experiments have revealed that methylammonium lead iodide (MAPbI 3 or CH 3 NH 3 PbI 3 ) materials show favorable gas-sensing properties to reducing gas NH 3 and oxidizing gases O 2 and O 3 . The first step to effective gas-sensing by using semiconductor materials for gas-sensing applications is to recognize a target gas through gas-solid interaction. To explore the sensing mechanisms of perovskite materials to different oxidizing and reducing gases, the changes of skeleton structures of MAPbI 3 in red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Central metal ion, which is Pb 2+ in all‐inorganic halide perovskite, is the main active site for interacting with the gas molecules. [ 64 ] In one representative study, it was confirmed that more Pb cations existing on the surface can enhance the adsorption of NO 2 molecules and their interaction with the sensing layer. [ 36 ] Therefore, the oxidation‐reduction properties of Pb can make a significant impact on the CsPbI 3 ‐NO 2 and CsPbBr 3 ‐NO 2 complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Central metal ion, which is Pb 2+ in all‐inorganic halide perovskite, is the main active site for interacting with the gas molecules. [ 64 ] In one representative study, it was confirmed that more Pb cations existing on the surface can enhance the adsorption of NO 2 molecules and their interaction with the sensing layer. [ 36 ] Therefore, the oxidation‐reduction properties of Pb can make a significant impact on the CsPbI 3 ‐NO 2 and CsPbBr 3 ‐NO 2 complexes.…”
Section: Resultsmentioning
confidence: 99%